LEGALITAS PEMBUATAN TRUST AGREEMENT DI INDONESIA - Ariwangsa, Dewa; Sukihana, Ida Ayu (Kertha Wicara : Journal Ilmu Hukum; Vol 11 No 1 (2021)DO - 10.24843/KW.2021.v11.i01.p01, 2022)
The purpose of this study is to analyze the legal arrangements of trust agreements in positive law and the legal aspects of making trust agreements in Indonesia. This normative legal research study was made using a historical approach, a conceptual approach and a statute approach. From the research that has been done, it was found that the legal arrangement of trust agreements in Indonesian positive law is based on the Financial Services Authority Regulation no. 27 /POJK.03/2015 concerning Bank Business Activities in the Form of Trust, as amended in conjunction with Financial Services Authority Regulation Number 25 /POJK.03/2016 concerning Amendments to Financial Services Authority Regulation No. 27/POJK.03/2015 concerning Bank Business Activities in the Form of Trust (hereinafter referred to as POJK Trust) which principally determines trust agreements as part of the banking legal regulatory regime. Furthermore, for trust agreements that are justified or can be said to be legal according to positive law, only trust agreements are carried out by individuals or legal entities as settlors or funders (assets) and the Bank as trustees or parties entrusted with managing the assets deposited in accordance with the provisions of POJK Trust.